Comparison of Trends of Resistance Rates over 3 Years Calculated from Results for All Isolates and for the First Isolate of a Given Species from a Patient - Lee, Sang-Oh (American Society for Microbiology, 2004)
We compared trends of annual resistance rates calculated from results for all isolates and for the first isolate of Staphylococcus aureus, Klebsiella pneumoniae, and Acinetobacter baumannii per patient over a 3-year period from 2001 through 2003. Antimicrobial susceptibility results of inpatients were extracted from a computerized database. Annual resistance rates of a species were calculated by two methods: (i) from results for all isolates, even those from patients with multiple isolates in a given year and (ii) from results for the first isolate from a patient in a given year, regardless of susceptibility profile or specimen type. Rates of methicillin-resistant S. aureus (MRSA) did not differ among all isolates (79.9, 78.8 and 79.6%; P = 0.86), but decreased for the first isolate per patient (70.2, 65.7, and 64.1%; P = 0.006) over time. Annual duplication rates of methicillin-susceptible S. aureus (MSSA) decreased (39.6, 37.6, and 31.7%; P = 0.01), but those of MRSA increased significantly (64.3, 67.8, and 68.9%; P = 0.004). Rates of cefotaxime-resistant K. pneumoniae did not differ over time by either method, and rates of imipenem-resistant A. baumannii decreased over time by both methods. Duplication rates did not differ for either susceptible or resistant isolates of K. pneumoniae and A. baumannii. The trends in MRSA rate differed by the two methods because of the different proportion of duplicate isolates per year. MRSA rates might be increasingly overestimated for all isolates. These results suggest that the method of calculating results for the first isolate per patient may remove the effect of duplication, allowing the simple and unambiguous analysis of cumulative susceptibility rates.